Epizoic diatom communities on chitons (Mollusca: Polyplacophora) and southern king crabs (Crustacea: Decapoda) from central coastal waters of San Jorge Gulf (Patagonian Sea, South Atlantic Ocean) - Rubén Agustín Lameiro; Adrián Oscar Cefarelli; Aimé Kimei Astrada; Amelia Alejandra Vouilloud (Lilloa, 2025)
Diatoms constitute one of the most diverse groups of marine microalgae worldwide, both free-living as well as associated associated with different types of substrata. In particular, marine benthic macroinvertebrates represent surfaces to which diatoms can attach. The present study aims to characterize the diversity of diatom communities associated with chitons and southern king crabs from coastal waters of San Jorge Gulf (South Atlantic Ocean), and to analyze possible differences in diatom diversity among those communities according to the animal substrata, the environment and season of the year. For this purpose, we conducted manual samplings to collect chitons from the intertidal, and sea diving samplings to collect southern king crabs from the subtidal at different sampling sites near Comodoro Rivadavia during winter 2018 and summer and winter 2024. Each specimen was carefully brushed and scraped to obtain microalgal material, which was subsequently processed using conventional methods and analyzed under both light microscopy (LM) and scanning electron microscopy (SEM). We estimated the relative abundance (%) of the identified diatom taxa as well as species richness (S), Shannon-Weaver diversity index (H´) and Pielou´s Evenness index (J) for each sample for comparison. Epizoic diatom communities included 43 taxa in Polyplacophorans and 62 in Decapods, mainly pennate diatoms with a scarce representation of centric diatoms. Solitary diatoms were the most frequent, with adnate, erect and motile forms recognized; various various morphological types of colonies were also recorded. We observed significant differences (?=0.05) in diatom diversity between the 2024 summer and winter for each invertebrate; however, no significant differences were found between the 2018 and 2024 winter samples. Polyplacophorans were studied for the first time as diatom hosts, and direct evidence of diatom attachment to the surface of both hosts is provided. This research study represents an important contribution to the knowledge of marine epizoic diatoms.